Risk Factors of Acute Pancreatitis in Oral Double Balloon Enteroscopy - Kopáčová, Marcela; Bureš, Jan; Rejchrt, Stanislav; Vávrová, Jaroslava; Bártová, Jolana; Soukup, Tomáš; Tomš, Jan; Tachecí, Ilja (Acta medica (Hradec Kralove), 2016)
Double balloon enteroscopy (DBE) was introduced 15 years ago. The complications of diagnostic DBE are rare, acute pancreatitis is most redoubtable one (incidence about 0.3%). Hyperamylasemia after DBE seems to be a rather common condition respectively. The most probable cause seems to be a mechanical straining of the pancreas. We tried to identify patients in a higher risk of acute pancreatitis after DBE. We investigated several laboratory markers before and after DBE (serum cathepsin B, lactoferrin, E-selectin, SPINK 1, procalcitonin, S100 proteins, alfa-1-antitrypsin, hs-CRP, malondialdehyde, serum and urine amylase and serum lipase). Serum amylase and lipase rose significantly with the maximum 4 hours after DBE. Serum cathepsin and procalcitonin decreased significantly 4 hours after DBE compared to healthy controls and patients values before DBE. Either serum amylase or lipase 4 hours after DBE did not correlate with any markers before DBE. There was a trend for an association between the number of push-and-pull cycles and procalcitonin and urine amylase 4 hours after DBE; between procalcitonin and alfa-1-antitrypsin, cathepsin and hs-CRP; and between E-selectin and malondialdehyde 4 hours after DBE. We found no laboratory markers determinative in advance those patients in a higher risk of acute pancreatitis after DBE.
Keywords: Lipase; Hyperamylasemia; pankreatitida; Amylases; Humans; alfa-1-antitrypsin; Case-Control Studies; Malondialdehyde; alpha 1-Antitrypsin; lidé středního věku; Risk Factors; dvojbalonová enteroskopie; C-reaktivní protein; studie případů a kontrol; kalcitonin; Female; rizikové faktory; Device assisted endoscopy; Double-Balloon Enteroscopy; C-Reactive Protein; lidé; Biomarkers; Calcitonin; Cathepsins; Double balloon enteroscopy; Small intestinal disorders; Deep enteroscopy; biologické markery; ženské pohlaví; E-selektin; Male; Middle Aged; Acute pancreatitis; amylasy; kathepsiny; Pancreatitis; mužské pohlaví; Acute Disease; hyperamylazemie; malondialdehyd; akutní nemoc; E-Selectin; lipasa